The spiritual and religious dimension of education and bringing-up - Valenkamp, M. (Koers, 2008)
In this article I will discuss the differences between the concepts “spirituality”, “religion” and “faith” and indicate the intertwinement of these dimensions of man’s mental life with bringing-up and education. Definitions of these concepts will not be given. Rather, their characteristics will be brought to the fore. The purpose of this article is to look for the essential relation of spirituality to the education and bringing-up of children. A so-called “religious matrix” will be worked out in which the core questions of spirituality and religion are to be expressed. By means of this matrix, a notion of the relation between spirituality, bringing-up and education will be formulated.